The broader autism phenotype in parents of children with autism - Kazantzidou, Panagiota; Costarelli, Vasiliki; Papanikolaou, George; Antonopoulou, Katerina (Psychology: the Journal of the Hellenic Psychological Society, 2025)
This review aims to provide a synopsis and analysis of the empirical evidence from research related to the study of the broader autism phenotype in parents of children with autism. This term refers to a condition that includes mild but qualitatively similar traits associated with autism spectrum disorder, involving deficits in communication, behavioural routines and resistance to change. In recent decades it has been suggested that these characteristics, which are quite often shared by parents and siblings of children with autism, may be useful in identifying environmental and genetic conditions associated with the disorder. A total of fourty-one studies published between 2012 and 2025 from the USA, Italy, China, Japan, Turkey, France, Iran, Australia, Belgium, the Netherlands, Portugal and England that met the predefined inclusion criteria were included. The results showed that the most frequently reported characteristics referred to social, communication and cognitive deficits, as well as various mental health conditions such as anxiety, depression and mood disorders. These findings could be useful for child psychiatrists and practitioners to contribute to the understanding of certain symptoms and, most importantly, help in the design and effective implementation of the intervention to strengthen the family of children with autism and improve their quality of life.